PEMBELAJARAN BAHASA ARAB: MENGUASAI KOSAKATA DASAR MELALUI METODE HAFALAN KONTEKSTUAL - Az-Zarqo, salsabila; Bilqis, Bilqis; Salsabila , salsabila; Raihany , Raihany (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2026)
Mastery of basic vocabulary is a crucial component in Arabic language learning, as it serves as the foundation for other language skills. However, in practice, vocabulary instruction often focuses on mechanical memorization without contextualization, causing vocabulary to be easily forgotten and difficult to apply in sentences. This study aims to improve students’ mastery of basic Arabic vocabulary through the application of the contextual memorization method. The research employed Classroom Action Research (CAR) with a descriptive qualitative approach and was conducted with seventh-grade students at a junior high school in an Islamic boarding school in Karawang during the odd semester of the 2025/2026 academic year. Data were collected through observation, interviews, and documentation. The learning activities included introducing vocabulary meanings, understanding singular and plural forms, reading contextual hiwar, providing sentence models, having students construct their own sentences, and conducting evaluations through exercises. The results indicate a significant improvement in students’ vocabulary mastery, as reflected in the increase in the average score from 65.46 to 87.86. In addition to improved learning outcomes, positive changes were observed in students’ learning behavior, including increased participation, motivation, and ability to use vocabulary appropriately in context. These findings demonstrate that the contextual memorization method is effective in helping students understand the meaning, function, and use of vocabulary in a more meaningful and applicable manner. Therefore, this method can serve as an alternative strategy for teaching Arabic vocabulary at the junior high school level